Rapid On-Site Detection of the Bursaphelenchus xylophilus Using Recombinase Polymerase Amplification Combined With Lateral Flow Dipstick That Eliminates Interference From Primer-Dependent Artifacts - Zhou, Qinzheng; Liu, Ya; Wang, Zheng; Wang, Huimin; Zhang, Xingyao; Lu, Quan (Frontiers in Plant Science, 2022)
The pine wood nematode (PWN), Bursaphelenchus xylophilus, is one of the most lethal nematode species, which causes pine wilt disease (PWD), a devastating forest disease. To date, no effective methods have been developed to control the disease; hence, rapid precise detection of B. xylophilus is of great significance. Traditional molecular diagnostic methods are time-consuming and require sophisticated instruments or skilled operators, which are unavailable in resource-limited settings. A specific, sensitive, and field-applicable diagnostic method is urgently needed. In this study, we developed a diagnostic method using recombinase polymerase amplification combined with lateral flow dipstick (RPA-LFD) for the rapid on-site detection of B. xylophilus. The false-positive signals from primer-dependent artifacts were eliminated using a probe, and base substitutions were included in the primer and probe. The entire detection process for the RPA-LFD assay can be completed under 38°C within approximately 30 min, including 15 min for crude nematode genomic DNA (gDNA) extraction and master mix preparation, 15 min for the RPA-LFD assay. This assay displayed high specificity toward B. xylophilus and showed no cross-reactions with closely related species, including Bursaphelenchus mucronatus and Bursaphelenchus doui. The sensitivity of this assay had a detection limit as low as 1 pg of B. xylophilus purified genomic DNA. Furthermore, the application of the RPA-LFD assay in simulated spiked pinewood samples showed accurate detection results. The RPA-LFD assay in this study successfully detected B. xylophilus in less than 30 min, providing a novel alternative for the simple, sensitive, and specific detection of B. xylophilus and showed potential for B. xylophilus point-of-care testing (POCT) in resource-limited areas or in field.